Production and energy efficiency of family units in agroecological transition: a case study from the West of Santa Catarina, Brazil - Neves, Ana Paula; Rios-Osorio, Leonardo Alberto; Funes-Monzote, Fernando (Sociedade & Natureza, 2018)
This study evaluated the behavior of the productive and energetic efficiency in family units in agro ecological transition, in the state of Santa Catarina - Brazil. The productive efficiency index was calculated by adding up the indicators of the production diversity, productive yield, number of people that the productive systems feed on energy and protein. The energetic efficiency index was calculated by adding up the indicators of the energy balance, energy cost for production of the protein, and the human workforce. The efficiency indexes show heterogeneity, from the seven units two of them showed low performance in both efficiencies, productive and energetic, three showed medium to high productive efficiency but low energetic. A unit showed low productive efficiency but high energetic, and in only one was observed high productive and energetic efficiency. In conclusion, the units studied are in follow an agroecological transition process, however they need to become functionally more efficient to advance and consequently to be more sustainable productively as well as energetically.